Micro and Nano Machining of Engineering Materials Recent Developments - Kumar, Kaushik; Zindani, Divya; Kumari, Nisha; Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers the recent developments in the production of micro and nano size products, which cater to the needs of the industry. The processes to produce the miniature sized products with unique characteristics are addressed. Moreover, their application in areas such as micro-engines, micro-heat exchangers, micro-pumps, micro-channels, printing heads and medical implants are also highlighted. The book presents such microsystem-based products as important contributors to a sustainable economy. The recent research in this book focuses on the development of new micro and nano manufacturing platforms while integrating the different technologies to manufacture the micro and nano components in a high throughput and cost effective manner. The chapters contain original theoretical and applied research in the areas of micro- and nano-manufacturing that are related to process innovation, accuracy, and precision, throughput enhancement, material utilization, compact equipment development, environmental and life-cycle analysis, and predictive modeling of manufacturing processes with feature sizes less than one hundred micrometers. .
Nano-machining and Micro- machining using conventional machining techniques -- Nano-machining and Micro- machining using non conventional machining techniques -- Materials in micro machining and nano machining -- Tools and processes for micro machining and nano machining -- Management of micro machining and nano machining processes -- Micro machining and nano machining enterprises -- Healthcare technologies and Environmental systems -- Advanced micro/ nanomachining processes -- Design of Micro and Nano sized products such as Microfluidic systems, Micro pumps, Micro engines etc -- Nanofinishing processes.
Keywords: Nanotechnology; Microtechnology; Microelectromechanical systems; Manufactures; Nanotechnology; Microsystems and MEMS; Machines, Tools, Processes